Effects of waste reduction strategy on firm performance: A survey of publishing firms in Kenya - Ochiri, George; Wario, Guyo; Odhiambo, Romanus; Arasa, Robert (International Journal of Economics, Commerce and Management United Kingdom, 2015)
This study focuses on the effect of waste reduction strategy on the performance of publishing firms in Kenya. Kenya is a regional publishing powerhouse (newspaper publications selling) in East and Central Africa. The industry contributes about 10% of the GDP and one of the fastest growing in the manufacturing sector. Unfortunately, Kenya does not produce most of the raw materials for publishing. In addition, the publishing industry in Kenya is faced with high rate of waste and returns. The study focused on the effect of adopting waste reduction strategy as a possible solution to the dwindling raw materials, increasing costs and high rate of returns. It used descriptive research design. The study population consisted of 357 firms from which a sample of 189 firms was taken using stratified random sampling and 138 responses were obtained. The data collection instrument was pre-tested before launching the final test. Empirical findings confirmed that indeed returns and wastes were high in publishing industry in addition to establishing that indeed adopting waste reduction would enhance performance of publishing forms. The study recommends that the firms view waste reduction as an investment with returns and not a cost.
Keywords: Waste reduction strategy; Publishing; Firm Performance; Reverse supply chain; Kenya